(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
This article presents data on the effects of different planting dates and mineral fertilizer application rates on plant height, growth and development, and the number of total and productive stems in winter barley varieties "Ikhtiyor", "Obikor" and "Kizilkurgan".